Hubungan Motivasi Berprestasi dan Perhatian terhadap Proses Kognitif pada Mahasiswa Tahun Pertama Jurusan Kesehatan Lingkungan Politeknik Kesehatan Maluku - Nurlaila Marasabessy; Yayi Suryo Prabandari; Ova Emilia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2013)
Background: Earlier data showed that the mean of achievement index at first year students in Environmental Health Polytechnic of Maluku were decreased for the last 3 years, from 2,9 at year 2008, become 2,6 at year 2010. Studentspresence rate in the first semester for science and skills subjects such as basic of environmental health, microbiology, patophysio-anatomy, and health entomology also decreased from 89,09% at 2008 to 77,04% at 2010. Several studies and experts concludes that both quality and quantity of student’s learning are influenced by some factors like achievement motivation, attention, and cognitive process. The decrease on that factors may influence quality and quantity of learning process. The objective of this study is to identify the correlations between achievement motivation and attention to student’s cognitive process at first year students of Environmental Health Polytechnic of Maluku.Method: This was a quantitative study using survey to 80 first year students academic year 2010/2011. It is used modified instrument Archer’s Health Professional Motivation Survey to assess achievement motivation, Attention Deficit/ Hyperactivity Disorder to assess attention, and Cognitive Processing Inventory to assess cognitive process. Correlation significance between factors analyzed by using Pearson Correlation.Results: There were significant correlations between achievement-motivation oriented to mastery learning and performance towards cognitive process. Attention factor also correlated to the cognitive process.Conclusion: Early stimulations of learning motivation and profession explanation are needed to the first year students. Learning methods that stimulate students engagement are important to improve the quality of student’s learning process.